Improving Integrated Management of Cereal Cyst Nematodes and other diseases in Central Western Asia and North Africa (CWANA) - CGIAR Research Program on Wheat (2021)
Study explored validated, region/disease-specific root rot management options based on breeders and pathologists experiences in Central West Asia North Africa (CWANA region).